2020
DOI: 10.1038/s41598-020-65518-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Analyses Reveal the Potential Mechanism of Pulmonary Injury Induced by Gallium Arsenide Particles in Human Bronchial Epithelioid Cells

Abstract: Extensive use of gallium arsenide (GaAs) has led to increased exposure to humans working in the semiconductor industry. this study employed physicochemical characterization of GaAs obtained from a workplace, cytotoxicity analysis of damage induced by GaAs in 16HBE cells, RNA-seq and related bioinformatic analysis, qRT-PCR verification and survival analysis to comprehensively understand the potential mechanism leading to lung toxicity induced by GaAs. We found that GaAs-induced abnormal gene expression was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“… 1 In the present study, the human bronchial epithelial cell line 16HBE was recruited for cell experiments, which has been widely used for COPD study in previous researches. 19 , 20 It was found that low expression of CASC2 was detected in both cell and cellular medium of CSE treated 16HBE cells, which was consistent with the results shown in the clinical serum samples. It is known that miRNAs are produced by all cell types, and the same miRNA may be derived from a variety of cell sources, such as endothelial cells, monocytes and macrophages, vascular smooth cells, and platelets, and eventually are secreted in blood.…”
Section: Discussionsupporting
confidence: 85%
“… 1 In the present study, the human bronchial epithelial cell line 16HBE was recruited for cell experiments, which has been widely used for COPD study in previous researches. 19 , 20 It was found that low expression of CASC2 was detected in both cell and cellular medium of CSE treated 16HBE cells, which was consistent with the results shown in the clinical serum samples. It is known that miRNAs are produced by all cell types, and the same miRNA may be derived from a variety of cell sources, such as endothelial cells, monocytes and macrophages, vascular smooth cells, and platelets, and eventually are secreted in blood.…”
Section: Discussionsupporting
confidence: 85%